Assessing the impacts of CPM emitted from stationary sources on PM2.5 source appointment of Wuhan, China. (1st April 2023) - Yuan, Chang; Wang, Zuwu; Cheng, Hairong; Chen, Jin; Liang, Shengwen; Su, Siqian; Wang, Pengcheng; Zhan, Yi; Jiang, Luxiang; Xiong, Ying
Graphical abstract: Highlights: Local emission inventory was improved by supplementing the CPM emissions. Contributions of stationary sources to PM2.5 concentrations were underestimated. Contributions of vehicle and secondary sulfate sources to PM2.5 were overestimated. Abstract: The condensable particulate matter (CPM) emissions from stationary sources have attracted widespread attentions due to its negative environmental impacts. In this study, we collected some CPM samples from fourteen different stationary sources in Wuhan based on the US EPA Method 202 for investigating emission factors (EFs) and source profiles of the CPM, as well as its impact on source apportionment of PM2.5 (particulate matter with aerodynamic diameters ≤ 2.5 µm). The CPM mass concentrations and chemical components including water-soluble ions, elements and organic fractions in the CPM were explicitly analyzed. Our results revealed that the emission level of CPM was 0.8 to 14 times that of filterable particulate matter (FPM). The EF of CPM from coal-fired power plant was 168.91 g/t of coal, that was about 1–28 times higher than other stationary sources tested in this study. Alkanes (4 %–35 %), esters (9 %–46 %), and water-soluble ions (24 %–64 %) were dominant chemical species in the CPM, which significantly differed from that of the FPM. As such, we built a new emission inventory that included CPM and applied it to the chemical mass balance (CMB) model for source apportionment of PM2.5 . The results showed that the contribution of stationary sources to PM2.5 increased from 17 % to 23 %, while the contribution of vehicle sources to PM2.5 decreased from 16 % to 11 % when considering the impact of CPM. In addition, isotope values of δ 13 C and δ 15 N in the CPM were measured to apportion the sources of carbon and nitrogen in aerosols. We found that the contributions of vehicle sources to carbon and nitrogen components in PM2.5 decreased by 3 % to 5 %, contribution of coal combustion sources increased by 6 % to 8 %, when considering the impact of CPM. Therefore, it is necessary to update emission inventory by including the CPM in further research for a greater accuracy of the source apportionment of PM2.5 . This study has important implications for achieving improved air quality management via emission mitigation of CPM from stationary sources at the local, regional, and national scales.